2020
DOI: 10.1386/jpme_00016_1
|View full text |Cite
|
Sign up to set email alerts
|

Student voice and choice in modern band curriculum development

Abstract: The perspectives and experiences of students should be considered first in the process of any significant curriculum reform. There is no one-size-fits-all approach to music education, and educators have a responsibility to design experiences that meet the needs of learners in their classroom. After hearing the individual voices of students in one New York State school district in the United States, the music faculty and authors developed modern band electives designed to increase access to school music and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Researchers have also studied the impact of modern band programs on K–12 school music participation. Clauhs and Cremata (2020) explored modern band programs in one New York State School District, examining district-level enrollment data for high school music ensembles both before and after the implementation of modern band classes. Their findings indicated that modern band classes greatly diversified the demographic profile of school music groups.…”
Section: Impact Of Modern Band On School Music Participationmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have also studied the impact of modern band programs on K–12 school music participation. Clauhs and Cremata (2020) explored modern band programs in one New York State School District, examining district-level enrollment data for high school music ensembles both before and after the implementation of modern band classes. Their findings indicated that modern band classes greatly diversified the demographic profile of school music groups.…”
Section: Impact Of Modern Band On School Music Participationmentioning
confidence: 99%
“…The introduction of modern bands has been shown to grow the overall participation in school music across all ensembles without detracting from enrollment in the traditional band, choir and orchestra programs (Clauhs & Cremata, 2020). This finding was consonant with those reported by Powell (2019b), who examined the impact of middle and high school modern band programs on school music participation.…”
Section: Impact Of Modern Band On School Music Participationmentioning
confidence: 99%
See 3 more Smart Citations